Legal Updates Regarding Industrial Design Rights for Micro, Small, and Medium Enterprises: A Pancasila Economic Perspective - Kadek Putri Nirmala Dewi; I Gede Agus Kurniawan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Industrial design is one of the important intellectual property rights for Micro, Small, and Medium Enterprises (MSMEs) as a strategic instrument in promoting the protection and development of product innovation, which is essential for the pillars of the national economy. This research aims to analyze efforts to reform laws related to industrial design rights for MSMEs from the perspective of Pancasila economics. This research is normative legal research with a conceptual and legislative approach. The research findings confirm that the status of industrial design rights is very important for SMEs in protecting and developing product innovation and creativity, which contributes to the national economy. Although Law No. 31 of 2000 does not differentiate between the protection of MSMEs and large businesses, this right provides exclusive protection against design to prevent plagiarism, while also strengthening the competitiveness of MSME products in domestic and international markets thru legal recognition of esthetic elements such as product packaging, shape, pattern, and color. From the perspective of Pancasila Economics, legal reforms that simplify registration procedures, reduce costs, and enhance technical assistance are crucial for creating regulations that are inclusive, fair, and adaptable to technological developments and globalization. This research recommends revising the Industrial Design Law to prioritize ease of access for MSMEs, while also affirming the role of industrial design rights as a strategic asset for empowering the people's economy in order to achieve social justice and sustainable national economic development.